How Are Cows Cooled on Dairy Farms in Florida? - Bethany Dado-Senn; Geoffrey E. Dahl; Jimena Laporta (EDIS)
While hot and humid conditions cause grief for dairy producers, additional impacts of heat and humidity on the dairy cow are sometimes overlooked. These conditions and their associated losses in productivity pose a growing concern to dairy producers, as more frequent and severe fluctuations in temperature, precipitation, and droughts are predicted to occur in the United States. This new 4-page document discusses heat stress in the dairy industry, the Florida dairy heat stress abatement survey, and heat stress abatement for lactating cows, dry cows, and dairy calves. Written by Bethany Dado-Senn, Geoffrey E. Dahl, and Jimena Laporta, and published by the UF/IFAS Department of Animal Sciences, April 2019. http://edis.ifas.ufl.edu/an355